IMPLEMENTASI STRATEGI PEMBELAJARAN BAHASA INGGRIS BERBASIS TOTAL PHYSICAL RESPONSE (TPR) DI SDN PAJAGALAN II SUMENEP - Laily Fajariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the challenges of teaching English in elementary schools, which often experience low student participation and difficulty in understanding the meaning of language when teaching is too focused on verbal explanations. This condition requires concrete strategies that are appropriate for the learning characteristics of lower grade students, one of which is through Total Physical Response (TPR), which coordinates language with physical responses. This study aims to describe the implementation of TPR-based English learning strategies in class III A of SDN Pajagalan II Sumenep, including the planning and implementation of activities, student responses and participation, and methods of evaluating understanding in practice. This study uses a descriptive qualitative approach. Data were collected through classroom observation, interviews with the principal and teachers, and documentation of learning tools and activities. The results showed that the TPR strategy was implemented through a series of instructions (commands), movement modeling by the teacher, repetition, group and individual response exercises, and instruction variation. Students tended to be more enthusiastic and engaged when learning was accompanied by physical actions, and the accuracy of responses increased after repetition and initial modeling. However, some students still needed support when the instructions became more complex, especially with combination commands. These findings indicate that TPR is effective in helping English learning become more active and meaningful for third-grade students, with the caveat that classroom management needs to be strengthened and the level of difficulty needs to be increased gradually.  Keywords: Total Physical Response (TPR), English Language Learning, elementary school, Learning Strategies